Pengaruh Akupresur Titik P6 Terhadap Mual Muntah Lambat Akibat Kemoterapi Pada Anak Usia Sekolah Dengan Leukemia Limfoblasitik Akut - Utami Tri Budi (Coping: Community of Publishing in Nursing, 2014)
Acupressure is one of the complementary therapy on children who are experience delayed chemotherapy-induced nausea and vomiting. Nausea vomiting is an effect that cause stress in children. The purpose of this ressearch was to determine the effect of acupressure P6 to delayed chemotherapy-induced nausea and vomiting in school-aged children with acute lymphoblastic leukemia in sanglah hospital. This study was a pre-experimental (one-group pre-post-test design). Sample consisted of 17 school children obtained from consecutive sampling. All respondent had been given acupressure with 30 times during 3 minute, it’s replay until total time is 15 minute. Before being given acupressure 13 (76,5%) chidren with severe nausea and vomiting, 4 (23,5%) chidren with moderate nausea and vomiting, and no chidren with low nausea and vomiting. After being given acupressure 12 (70,6%) chidren with low nausea and vomiting, 5 (29,4%) chidren with moderate nausea and vomiting, and no chidren with severe nausea and vomiting. Based on the Wilcoxon Signed Rank Test, this difference was statistically significant, with p value 0,000 (p?0,05), which mean there is an influence of acupressure P6 to delayed chemotherapy-induced nausea and vomiting in school-aged children with acute lymphoblastic leukemia in Sanglah hospital. The conclusion of the research was the acupressure can be applied as a non-pharmacological therapy to reduce nausea and vomiting caused by chemotherapy in children.